Anemia pada Kehamilan: Dampak Klinis, Komplikasi, dan Strategi Manajemen - Asyima Asyima; Noviyani Hartuti (Pusat Riset dan Inovasi Nasional, 2025)
Anemia during pregnancy is a significant maternal health issue with serious impacts on maternal and perinatal outcomes, including complications such as severe preeclampsia, postpartum hemorrhage, and low birth weight (LBW), all of which contribute to increased morbidity and mortality rates. This literature review aims to analyze the clinical impacts of pregnancy anemia, related complications, and effective management strategies based on the latest scientific evidence (2020-2024). The study examines the relationship between anemia and preeclampsia, LBW, and postpartum hemorrhage, as well as the importance of nutritional fulfillment in prevention and management. Five research articles from indexed journals were collected from the Scopus database, with inclusion criteria of studies with clear designs, focusing on pregnancy anemia, and published in Indonesian or English. The analysis results show that pregnancy anemia is a predisposing factor for preeclampsia through mechanisms such as placental hypoxia and oxidative stress. Anemia is also closely related to an increased incidence of LBW and postpartum hemorrhage, particularly due to lower hemoglobin reserves and uterine contractility issues. Adequate nutritional fulfillment is influenced by socioeconomic barriers, supplementation side effects, and lack of family support. Anemia management requires a comprehensive approach, including routine screening, prophylactic supplementation, nutritional education, and effective referral systems for complex cases. Prevention through early detection and timely intervention is crucial in reducing maternal and perinatal morbidity.